ANALISIS BISNIS SEBAGAI SALAH SATU INFORMASI PENTING BAGI STAKEHOLDERS - Yuliawati Tan (Journal of Management and Business, 2005)
Financial statement is one of the most important information which can be used by management and company's stakeholders as a basts for decision making. Business analysis, in the other hand, is the study of all aspects of the firm and its environment. Business analysis and financial statement analysis work hand in hand to help managers and stakeholders in understanding the target firm's potential. Business analysis will highlight issues that need to be studied further in the financial statement analysis stage. Likewise, financial statement analysis identifies concerns that require more detailed business analysis.